COVID-19 infection among dentists in Iraqi Kurdistan Region - Salih Hosoglu; Mohammed Khalid Mahmood (Journal of Infection in Developing Countries)
Introduction: COVID-19 incidence was relatively high among dentists in Iraq, reflecting the high number of cases in the community. Therefore, possible epidemiological features of COVID-19 infection were investigated among dentists in Iraqi Kurdistan Region.